1980
DOI: 10.1103/physrevc.21.972
|View full text |Cite
|
Sign up to set email alerts
|

12.3-minCf256and 43-minMd

Abstract: The new isotope 12.3-min ' Cf was produced via the ' Cf(t,p) reaction, and a new 43-min isomer of ' Md was produced via the ' Es(a,n) reaction. The fragment mass and kinetic energy distributions from the spontaneous fission of" Cf were found to be very similar to those from the spontaneous fission of lighter Cf isotopes. The mass division is primarily asymmetric, and the average total kinetic energy is 189.8+0.9MeV. The 43-min "Md presumably decays by electron capture and provides an opportunity to study the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 21 publications
10
31
0
Order By: Relevance
“…Whichever valley is eventually followed by the spontaneously fissioning nucleus towards scission, the outcome is the same in terms of mass fragmentation since in either valley the configurations are left-right symmetric. This leads thus to a symmetric mass distribution, as was obtained in all the other theoretical sudies and in agreement with experiment [6,7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Whichever valley is eventually followed by the spontaneously fissioning nucleus towards scission, the outcome is the same in terms of mass fragmentation since in either valley the configurations are left-right symmetric. This leads thus to a symmetric mass distribution, as was obtained in all the other theoretical sudies and in agreement with experiment [6,7].…”
Section: Discussionsupporting
confidence: 90%
“…Based on the results from the Argonne group published the following year [4] and showing the asymmetric character of the spontaneous fission of 256 Fm, they concluded that "symmetric mass division in low-energy fission of heavy actinides appears abruptly at 257 Fm". This was confirmed later in the measurements by Hulet and collaborators [5,6,7] who found very narrow symmetric mass distributions in the spontaneous fission of 258 Fm and 259 Fm.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In Fig. 5 (b), we compare our E x = 7.5 MeV result with 258 Fm spontaneous fission data [26] and n th + 257 Fm fission data [27]. A strong single peak component can be seen in both experimental data.…”
Section: Fig 5 (B) Shows the Ffmd Formentioning
confidence: 82%
“…We have performed several experiments in which the actin1de products from the interactions of 18 o, 86 Kr and 136 xe with 248 cm were ch~mically isolated and their cross sections determined. We use these data, along with literature results from the 48 ca + 248 cm systeml,lO and from the 238 u .…”
Section: Introductionmentioning
confidence: 99%